Model'nye orientiry dlja programm razvitija olimpijskich vidov sporta v Rossijskoj Federacii - Timofeev, V. D. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The relationships between the most important target indicators of sports development programs were investigated. The data was taken from the state statistical report "Information on sports schools" (Form No. 5-FC) for 2012. The sample included 25 types of summer non-game sports, including 19 sports in which Russian athletes won prizes at the 2012 Olympics. A strong statistical relationship (r >/= 0.7; p </= 0.00018) was revealed between the results at the Olympics and the 3rd indicators. These indicators included the total number of coaches, the total number of departments by sport school (CSP, etc.), the total number of athletes at the training stages. Along with this, the calendar of events (competitions, mass events) for 2019, implemented by regional judo federations in 59 subjects of the Russian Federation, was studied. A weak statistical relationship was found (r = 0.424; p = 0.0008) between the number of events in the calendar plans and the number of judo practitioners in the regions.Meanwhile, a strong statistical relationship was found (r = 0.963; p = 2.62289E-34) between the number of judokas and the number of trainers in this sport. Model guidelines of the most important target indicators were calculated using pairwise regression equations. To win a total of 2 Olympic medals, it is necessary: 237 sports departments, 1,073 coaches in these departments and more than 36,000 athletes at various stages of training. It is recommended that model guidelines be taken into account when sports federations will make sports development programs in the Russian Federation.